THE ANALYSIS OF THE TYPES OF COMMUNICATION STRATEGY USED BY THE TEACHER IN TEACHING THE SEVENTH GRADE STUDENTS OF SMP LAB UNIVERSITAS PENDIDIKAN GANESHA - Suari, D.A.B (Universitas Pendidikan Ganesha, 2019)
This study aimed at describing the types of communication strategy used by the teacher of SMP LAB Singaraja in teaching seventh grade students, the most frequent types of communication strategy used and the teacher’s reasons in using those strategies. This study was designed as a descriptive qualitative. The sample of this study was a teacher in SMP Lab Singaraja who teaches the seventh grade students in that school. The data was collected by field recording, interview, and observation sheet. The result of this study shows that comprehension check was the most frequent strategy used in the learning process with total occurrence of 7 times, followed by language switching 5 times, approximation 4 times, paralanguage 3 times, topic avoidance 2 times and then both clarification request and circumlocution occurred 1 time.